Financial disbalances in the regional economy: analysis of causes and consequences - Kloba, Taras (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The article is devoted to the study of the analysis of the causes and consequences of financial imbalances in the economy of the regions. The purpose of the paper is to analyze the causes and consequences of financial imbalanced in the region's economy, to consider scenarios for the development of financial imbalanced, and to identify the main goals of the development of financial imbalanced and ways to achieve them. The object of the study is a certain system of indicators on the analysis of financial imbalances in the regions of Ukraine. The theoretical and methodological basis of the research is the diagnosis of indicators of financial imbalances in the economy of regions that characterize the economic development of the region's economy, namely: the number of economic entities, the volume of sales of goods (goods, services) of economic entities; the volume of retail trade, the volume of foreign trade in goods, the index of capital investments, the index of industrial products, the index of construction products, the consumer price index both in Ukraine and regions for 2013-2017 years. Based on the results of the assessment, the reasons for the financial imbalancees that arose in Ukraine during the crisis phenomena from 2014 were substantiated, an analysis of the causes of these imbalances and their forms and the impact on the stability of the financial system of the regions and the economy of the state as a whole is necessary not only to overcome the consequences of the current crisis , but also for counteracting possible crisis phenomena in the future. Scientific novelty consists in systematizing a certain number of indicators for the analysis of financial imbalances in the region's economy, and their influence on the development of regions and Ukraine as a whole is considered. The main ways to determine the causes and consequences of the planned regional economic policy, which takes into account the specifics of regions in the most important industries and aimed at solving problems that impede economic development. Along with this, the reasons and consequences of financial imbalanced in the region's economy are substantiated, as well as criteria for assessing the effectiveness of indicators that directly affect financial imbalanced in the economy of Ukraine and regions in particular. Conclusions: trends and prospects for the development of financial imbalanced in the regional economy are very important for the regions, which contributes to the formation of a balanced structure of the regional economy. Thus, the stability of the economic development of financial imbalanced implies the existence of unity, autonomy and integrity.